Farmer participatory pond based cage aquaculture for raising fish seed in South Garo Hills, Meghalaya, India - Das, S. K.; Samajdar, T.; Das, Amit; Islam, M. (Indian Journal of Fisheries, 2017)
Fingerling sized fish seeds are always in great demand for any type of aquaculture operations. The paper highlights the results of a maiden study undertaken to popularise pond based cage culture for raising fingerling sized fish seed aimed at stocking quality fish fingerlings for augmenting fish production in the Garo Hills of Meghalaya. A farmer participatory study was undertaken for raising fry to fingerling sized fish seeds of 3 fish species viz., silver carp (Hypophthalmichthys molitrix), gonius (Labeo gonius) and common carp (Cyprinus carpio) in pond based cages during September-November 2011. Fry sized fishes of these species were reared in locally made bamboo-net cages (2 x 1.5 x 2 m) at different stocking densities. The primary objective was to increase the survival rate and observe the comparative growth rate of different species under varied stocking densities. A total of 18 cages were grouped under 3 stocking densities viz., 150, 250 and 300 fry m-3. Highest survival rate was observed at a stocking density of 150 fry m-3 for all the three species. Among the three species, silver carp demonstrated the highest survival rate at all the stocking densities. In terms of growth, better performance was observed with stocking density of 250 fry m-3 for all species.